PERANCANGAN ALAT PENGUBAH ARUS DC KE AC BERBASIS MIKROKONTROLER SEBAGAI PENGGANTI PAGAR KEBUN - Ardiansa; Ayu Annisa Akbar (Universitas Islam Balitar, 2021)
Farming is the main source of livelihood of Indonesians living in rural areas, one of which is corn. Corn yields are influenced by many factors, among others, the ever-changing climate, water availability, soil fertility, crop management systems and so on. At the time of initial observation to the farmer group failure is often also experienced due to the disruption of pig pests at night. So that a system is needed that can control the handling of pig pests by making traps using a stun tool. To convert DC (Direct Current) current into AC (Alternating Current) can be done with a series of power transistors. The power transistor designed is using the flip-flop method, both transistors will work alternately, this type of change includes a phase changer. The goal in this study was to create a microcontroller-based garden fence control device. This tool is able to provide an alternative in making it easier for farmers to control the land so as to avoid pig pests. The results of the trial DC current changer to AC d field is very well functioning so that farmers no longer experience pig pest disturbances at night.